Limited applicability of cathepsin D for the diagnosis and monitoring of non‐alcoholic steatohepatitis. Issue 5 (4th April 2019) - Kamarajah, Sivesh K; Khoo, Stanley; Chan, Wah‐Kheong; Sthaneshwar, Pavai; Nik Mustapha, Nik Raihan; Mahadeva, Sanjiv
Abstract : Background and Aim: To date, there are limited data on the applicability of cathepsin D for the diagnosis and monitoring of non‐alcoholic steatohepatitis (NASH). Methods: This study included patients with biopsy‐proven non‐alcoholic fatty liver disease (NAFLD) diagnosed between November 2012 and October 2015. Serum cathepsin D levels were measured using the CatD enzyme‐linked immunosorbent assay (USCN Life Science, Wuhan, China) using stored samples collected on the same day of the liver biopsy procedure. The performance of cathepsin D in the diagnosis and monitoring of NASH was evaluated using receiver operating characteristic analysis. Results: Data for 216 liver biopsies and 34 healthy controls were analyzed. The mean cathepsin D level was not significantly different between NAFLD patients and controls; between NASH and non‐NASH patients; and across the different steatosis, lobular inflammation, and hepatocyte ballooning grades. The area under receiver operating characteristic curve (AUROC) of cathepsin D for the diagnosis of NAFLD and NASH was 0.62 and 0.52, respectively. The AUROC of cathepsin D for the diagnosis of the different steatosis, lobular inflammation, and hepatocyte ballooning grades ranged from 0.51 to 0.58. Of the 216 liver biopsies, 152 were paired liver biopsies from 76 patients who had a repeat liver biopsy after 48 weeks. There was no significant change in the cathepsin D level at follow‐up compared to baseline in patients who had histological improvement or worsening for steatosis, lobular inflammation, and hepatocyte ballooning grades. Cathepsin D was poor for predicting improvement or worsening of steatosis and hepatocyte ballooning, with AUROC ranging from 0.47 to 0.54. It was fair for predicting worsening (AUROC 0.73) but poor for predicting improvement (AUROC 0.54) of lobular inflammation. Conclusion: Cathepsin D was a poor biomarker for the diagnosis and monitoring of NASH in our cohort of Asian patients, somewhat inconsistent with previous observations in Caucasian patients. Further studies in different cohorts are needed to verify our observation. Abstract : To date, there are limited data on the applicability of cathepsin D for the diagnosis and monitoring of non‐alcoholic steatohepatitis (NASH). Cathepsin D was a poor biomarker for diagnosis and monitoring of NASH in our cohort of Asian patients, somewhat inconsistent with previous observations in Caucasian patients.